Strategi Pengelolaan Gazebo sebagai Prasarana Wisata dalam Meningkatkan Daya Tarik Kunjungan di Pantai Pasir Putih Parparean II Kabupaten Toba - Melisa Manurung; Tio R. J. Nadeak; Yulia Kurnia Sari Sitepu; Elisamark Sitopu; Rusmauli Simbolon (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2026)
This study aims to describe gazebo management strategies as tourism infrastructure to increase visitor attraction at Pasir Putih Parparean II Beach, Porsea Subdistrict, Toba Regency. The beach is a unique destination in the Lake Toba area, characterized by fine white sand that is rarely found in the region. However, visitor data from the Toba Regency Tourism Office reveals a significant decline, from 35,304 visitors in January–April 2023 to only 1,550 visitors in January–August 2025. This decline is closely linked to the unplanned construction of permanent gazebos on the beach area, which has reduced the open space that constitutes the beach’s main attraction. This study employed a descriptive qualitative method. Data were collected through in-depth observation, semi-structured interviews, and documentation. The key informants consisted of three beach managers: Herbert Napitupulu, Nora Pandiangan, and Her Hutasoit, selected purposively based on their direct involvement and in-depth knowledge. Two regular tourists were also included as additional informants. Data analysis followed the Miles and Huberman model, encompassing data reduction, data presentation, and conclusion drawing. The results indicate that gazebo management strategie including facility improvements, environmental landscaping, and the provision of supporting amenities contribute significantly to enhancing visitor comfort and tourism appeal. This study recommends more systematic and planned management, spatial restructuring of gazebo placement, and the implementation of effective promotional strategies to support Pasir Putih Parparean II Beach as a sustainable tourism destination.